Revitalisasi Rumah Dodol di Kabupaten Buleleng : Program Kemitraan Masyarakat - Putu Sukma Megaputri; Putu Dian Prima Kusuma Dewi; Cindy Meilinda Sari; Ari Pertama Watiningsih; I Made Sundayana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Dodol is one of the traditional foods from all regions in Indonesia, one of which is Bali. However, some dodol houses do not pay attention to health factors, cleanliness in the process of manufacture, packaging and marketing. The aim of this service is to revitalize dodol houses in Kubutambahan and Penglatan Villages. The method of community service uses the technology application method. The targets were dodol houses in Kubutambahan and Penglatan Villages. The results found were solutions to problems in the form of a solution plan and the outcomes that had been carried out. Currently the dodol house has been revitalized using a modern stove, with workers using PPE to maintain cleanliness and nutritional value in the manufacturing process. Substituting artificial sweeteners and dyes for natural ingredients. In addition, marketing is also carried out without conventional methods so that marketing can be carried out in all directions.